2015
DOI: 10.1117/1.jbo.20.3.036014
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic-imaging technique for subsurface quantification of near-infrared markers during surgery

Abstract: Obtaining accurate quantitative information on the concentration and distribution of fluorescent markers lying at a depth below the surface of optically turbid media, such as tissue, is a significant challenge. Here, we introduce a fluorescence reconstruction technique based on a diffusion light transport model that can be used during surgery, including guiding resection of brain tumors, for depth-resolved quantitative imaging of near-infrared fluorescent markers. Hyperspectral fluorescence images are used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Wide-field, fluorescence-guided surgery limitations include ( 184 ) ambiguity at the margins where fluorescence intensity decays and difficulty of visualization on the sides of a resection cavity and shaded areas in the surgical wound. Further limitations include fluorescence absorbance by blood and tissue layers ( 197 ), insufficient fluorescence intensity in >95% of low-grade gliomas ( 107 , 198 , 199 ), and lack of quantitative assessment of fluorescence intensity. In PpIX fluorescence visualization, PpIX is quantitatively related at the microscopic level to increasing malignancy in both low- and high-grade gliomas ( 117 ).…”
Section: Instrumentation For Fluorescence-guided Resectionmentioning
confidence: 99%
“…Wide-field, fluorescence-guided surgery limitations include ( 184 ) ambiguity at the margins where fluorescence intensity decays and difficulty of visualization on the sides of a resection cavity and shaded areas in the surgical wound. Further limitations include fluorescence absorbance by blood and tissue layers ( 197 ), insufficient fluorescence intensity in >95% of low-grade gliomas ( 107 , 198 , 199 ), and lack of quantitative assessment of fluorescence intensity. In PpIX fluorescence visualization, PpIX is quantitatively related at the microscopic level to increasing malignancy in both low- and high-grade gliomas ( 117 ).…”
Section: Instrumentation For Fluorescence-guided Resectionmentioning
confidence: 99%
“…Previous studies exploring the ability of red-light–excited fluorescence to detect subsurface PpIX in tissue-simulation phantoms have demonstrated PpIX detection at depths of up to 5 mm, with either a fiber optic point-spectroscopy probe or a wide-field imaging system. 4,10 Fluorophore visualization at such a depth may well have practical benefit, countering the common obscuration of parts of the resection surface by blood or necrotic tissue. Strategies, instrumentation, and algorithms capable of assessing the depth and quantity of subsurface fluorophore are under development.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that this model can be used not only in pointlike fluorescence depth estimation but also in topographic mapping of subsurface fluorescence depth. 23 This depth retrieval technique requires reduced scattering and absorption coefficients of the tissue to be known a priori. Table 1 demonstrates optical properties of chicken breast tissue for two different wavelengths.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, eq is of the linear form, in which the logarithm of fluorescence ratio at two wavelengths linearly depends on the depth of fluorescent source under the tissue. It has been demonstrated that this model can be used not only in pointlike fluorescence depth estimation but also in topographic mapping of subsurface fluorescence depth . This depth retrieval technique requires reduced scattering and absorption coefficients of the tissue to be known a priori.…”
Section: Methodsmentioning
confidence: 99%